How to jointly control a ball trajectory on a moving board: Methodological insights into Motor Learning and Rehabilitation - Anaëlle Cheillan; David M. Jacobs; Pedro Passos (PLoS ONE, 2025)
Motor (re-)learning can be assessed using various conceptual and methodological frameworks, each of which portrays the learner’s abilities in different ways. The present paper investigates how the direct learning theory can be applied to the assessment of perception-action couplings required for a highly-dimensional joint-action task. Eleven novice dyads were instructed to stand on an unstable surface (BOSU), while jointly manipulating a board with the aim to make a ball roll along a target. Ball and board’s three-dimensional movements were recorded with an 8-camera motion capture system. Linear regression analyses were conducted to examine how task performance – using ball kinematics – and dyadic behaviour – using board kinematics – evolved with practice. Correlation analyses between movement and informational variables were used as a first step to build information spaces. Information spaces are a direct learning tool developed to investigate how the available information is exploited when practicing a new motor task. With practice, dyads reduced the variability in task-irrelevant degrees of freedom, while increasingly coupling the task-relevant degrees of freedom to more optimal informational variables. Finally, information spaces were discussed as a valuable tool for assessing and guiding the re-learning of perception-action in rehabilitation.